A reader's guide to modern American drama - Sternlicht, Sanford V. (Syracuse, N.Y. : Syracuse University Press, 2002)
Surveys the history of modern American drama, examining the work of over seventy playwrights, and discussing the various factors that have influenced American theater from Victorian times through the twentieth century.
Includes bibliographical references and index.
Reference and Research Book News.
Adult
Keywords: American drama -- 20th century -- History and criticism -- Handbooks, manuals, etc; Theater -- United States -- History -- 20th century -- Handbooks, manuals, etc; American drama -- History and criticism -- Handbooks, manuals, etc; Theater -- United States -- History -- Handbooks, manuals, etc